Juglone extraction from walnut (Juglans regia L.) green husk by supercritical CO2: Process optimization using Taguchi method. Issue 3 (June 2020) - Ramezani, Nima; Raji, Foad; Rezakazemi, Mashallah; Younas, Mohammad
Graphical abstract: Abstract: In this work, the supercritical CO2 extraction of Juglone from the walnut green husk (WGH) using ethanol as co-solvent has been studied. The effects of pressure (90−150 bar), temperature (35–50 ℃) and particle size (375−1500 μm) on Juglone extraction were investigated by the Taguchi method with L9 orthogonal array (three factors in four levels). Gas chromatography–mass spectroscopy (GC–MS) revealed that an increase in pressure from 90 to 150 bar improved the extraction efficiency up to 38.24 % while enhancement of temperature and particle size had a negative influence on the value of extracted Juglone. The highest extracted Juglone was 37.26 mg which was obtained at optimum conditions of 150 bar, 35 ℃, and 375 μm. Results from variance analysis (VA) indicated that pressure is the most significant factor in the amount of extracted Juglone by 56.46 % contribution while temperature has the least influence by 6.88 % contribution.